Fieldwork and Public Archaeology (or: Why Even the Seemingly Clear Connections Should Be Examined?) - Tatjana Cvjetićanin (University of Belgrade, 2019)
Public archaeology and community archaeology are some of the terms denoting various ways in which archaeologists, convinced that archaeology should not act in isolation, reach out to the public or include it into disciplinary practices. The public is principally educated and enabled to embrace the social relevance of archaeology.